On the presence of gypsum in the archaeological burial site of Cova des Pas (Menorca, western Mediterranean). (January 2015) - Bergadà, M. Mercè; Poch, Rosa M.; Cervelló, Josep M.
Abstract: The Cova des Pas (Ferreries, Menorca) is a cave that was used as a collective sepulcher during the late Bronze Age (1100–800 B.C.). Apart from the archaeological and paleoanthropological attractiveness of the site, it stands out for its excellent preservation of organic remains. In this paper we study the micromorphology of the human and organic remains in order to assess the preservation conditions and in particular to elucidate the presence of gypsum, found mainly on human remains, plant fibers and shrouds. In order to do this, a detailed description of the geological and geomorphological environment of the cave is provided. Gypsum is present as microcrystalline gypsum resulting from diagenetic process in this cave. Due to the lack of any other gypsum source, and based on its location and morphology, the gypsum is interpreted to be a consequence of the oxidation of organic sulphur from the buried bodies which later precipitated with the calcium present in the substrate. The location, morphology and lithology of the deposit have contributed to the arid environmental conditions, thus avoiding the leaching of gypsum and favouring the preservation of the remains and materials of organic origin, which is rare in archaeological contexts. Highlights: We found microcrystalline gypsum nodules and infillings in human remains. The source of gypsum is the oxidation of organic sulphur from the buried bodies. The aridity contributed to preservation of the organic remains and their gypsum content.